Digital Technology Integration in Management Accounting: A Literature Review of Challenges and Opportunities - Oktaviyah, Nurafni (Universitas Negeri Makassar, 2025)
The development of digital technology has driven significant transformations in management accounting practices. Technologies such as big data analytics, artificial intelligence (AI), robotic process automation (RPA), cloud computing, the Internet of Things (IoT), and blockchain have transformed the way organizations collect, process, and analyze information for decision-making. This literature review aims to identify forms of digital technology integration in management accounting, analyze the resulting opportunities, and examine the challenges faced by organizations. Using a narrative literature review method based on publications from 2018–2025, this study finds that digital technology contributes significantly to improving information quality, business process efficiency, and enhancing the strategic role of management accountants. However, significant challenges remain, such as limited human resource competency, investment costs, organizational resistance, data security issues, and the lack of standardized standards. This study provides direction for further research and recommendations for companies developing digital-based management accounting systems.